HSV-1 ICP22 condensates impair host transcription by depleting promoter RNAPII Ser-2P occupation - Qi, Hansong; Yin, Mengqiu; Ren, Xiaoli; Chen, Guijun; Li, Ai; Li, Yongxia; Cao, Xia; Zhou, Jumin (Frontiers in Microbiology, 2025)
Herpes simplex virus type I (HSV-1) infection-induced host transcript ion shutdown is one of the most critical hallmarks of viral lytic infection. However, how HSV-1 and which viral factors accomplish this dramatic effect is not well understood. In this study, we show that ICP22-defined condensates shutdown host global transcription but facilitate viral transcription. This is independent of its effects on viral infection-triggered changes in splicing, readthrough, and read-in events. ICP22 condensates depleted the serine-2 phosphorylated RNA polymerase II (RNAPII Ser-2P) occupancy from the host transcription start site (TSS), resulting in decreased host transcripts output. At the same time, it ensures proper RNAPII Ser-2P distribution on the viral genome to promote viral transcription. This effect is dependent solely on the condensate-forming activity, as condensate-disrupting point mutations abolish it. In addition, ectopic expressed ICP22 alone could decrease host transcription activity and increase histone H3K27me3 modification level. Thus, ICP22 condensates shut down host transcription by reducing RNAPII binding to host TSS to impair the host transcription.